2021
DOI: 10.3389/fpsyt.2021.735523
|View full text |Cite
|
Sign up to set email alerts
|

Study Protocol for “Psilocybin as a Treatment for Anorexia Nervosa: A Pilot Study”

Abstract: Background: Anorexia nervosa (AN) is a serious and life-threatening psychiatric condition. With a paucity of approved treatments, there is a desperate need for novel treatment avenues to be explored. Here, we present (1) an overview of the ways through which Public Patient Involvement (PPI) has informed a trial of psilocybin-assisted therapy for AN and (2) a protocol for a pilot study of psilocybin-assisted therapy in AN currently underway at Imperial College London. The study aims to assess the feasibility, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 137 publications
(149 reference statements)
0
24
0
1
Order By: Relevance
“…Enhanced psychological flexibility induced by psychedelic therapy has been proposed as a potential therapeutic mechanism of psychedelic therapy in eating disorders (321). While a preliminary study suggested a benefit of psychedelic therapy in improving depression and well-being scores in people with a self-reported lifetime diagnosis of an eating disorder (16), we await results from ongoing clinical trials (Table 3) to determine whether psychedelic therapy will lead to clinically meaningful benefits in those with eating disorders (322). It is worth noting the possibility that psychedelic therapy may be of utility for disorders related to compulsive overeating, perhaps better categorized as food addiction.…”
Section: Eating Disordersmentioning
confidence: 99%
“…Enhanced psychological flexibility induced by psychedelic therapy has been proposed as a potential therapeutic mechanism of psychedelic therapy in eating disorders (321). While a preliminary study suggested a benefit of psychedelic therapy in improving depression and well-being scores in people with a self-reported lifetime diagnosis of an eating disorder (16), we await results from ongoing clinical trials (Table 3) to determine whether psychedelic therapy will lead to clinically meaningful benefits in those with eating disorders (322). It is worth noting the possibility that psychedelic therapy may be of utility for disorders related to compulsive overeating, perhaps better categorized as food addiction.…”
Section: Eating Disordersmentioning
confidence: 99%
“…Taken together, and with the relevant literature on ketamine, these findings underscore the desire to develop and test psychedelic interventions for EDs, as well as their potential therapeutic value. Findings additionally emphasize key methodological considerations in trial design, which have already begun to inform study protocols [134].…”
Section: Future Perspectives and Directionsmentioning
confidence: 92%
“…Taken together, and with the relevant literature on ketamine, these findings underscore the desire to develop and test psychedelic interventions for EDs, as well as their potential therapeutic value. Findings additionally emphasize key methodological considerations in study design, which have already begun to inform study protocols [153] and ongoing clinical trials (Identification No. NCT04714541, NCT04661514, NCT05035927, NCT04052568, NCT04505189, and NCT04454684).…”
Section: Future Perspectives and Directionsmentioning
confidence: 93%